The End of International Adoption? : an Unraveling Reproductive Market and the Politics of Healthy Babies - Fenton, Estye (Families in Focus Ser., 2019)
Since 2004, the number of international adoptions in the United States has declined by more than seventy percent. In The End of International Adoption? Estye Fenton studies parents in the United States who adopted internationally in the past decade during this shift. She investigates the experiences of a cohort of adoptive mothers who were forced to negotiate their desire to be parents in the context of a growing societal awareness of international adoption as a flawed reproductive marketplace. Many parents, activists, and scholars have questioned whether the inequality inherent in international adoption renders the entire system suspect. In the face of such concerns, international adoption has not only become more difficult, but also more politically and ethically fraught. The mothers interviewed for this book found themselves navigating contemporary American family life in an unexpected way, caught between the double-bind of work-family life and a new paradigm of thinking about the method--international adoption--that they used to create those families.